Pengaruh Likuiditas Terhadap Rentabilitas (Studi Kasus Di Perusahaan Umum Perikanan Indonesia Cabang Brondong Lamongan Tahun 2014-2019 ) - Ahmad Faishol (Center for Research and Community Service (LPPM) University of Abulyatama, 2020)
This study aims to determine the effect of liquidity on profitability in Indonesian general fisheries companies in the Brondong branch. This type of research is quantitative research. Based on the results of the analysis, it can be concluded that there is a significant influence between liquidity on profitability, it is shown. 5,786> -4.30265. solvency variable (X2) has an effect on profitability (Y), 040 <0.05, and the value of tcount> ttable is 4.858> 4.30265. working capital variable (X3) has an effect on profitability (Y), 031 <0.05, and the value of tcount> ttable is 5.584> 4.30265. this is because the size of the profitability is influenced by the size of the liquidity, solvency, and working capital.